The Effect of Speech Act of Promising in Communication in Jouf University - A Case Study - Halemeh Bani-Abdo,; Malini Ganapathy, (Journal of Human Development and Communication (JoHDeC), 2025)
The present study dealt with the realization of the promising speech act in Saudi Arabia in southern region. It is a qualitative study; it is applied in Jouf University. The study has chosen 8 female Saudi students and conducted two focus group discussions (hereafter FGD). The sessions of the FGD were conducted orally and audio- recorded. The population of the study were chosen randomly from the 3rd and the 4th year- 5th, 6th,7th and 8th level from English Department in Jouf University in Tabarjal. Further, the collected data was transcribed by using NVivo software-12 version. Then, thematic analysis was used to analysed data collected. Mainly, the study discussed the different replies to each question provided by each respondent. The functions of speech acts were highlighted. The cultural communicative theory was applied as a scale to judge the different replies. A highlight was spot on the impact of the Islamic culture on promising. Briefly, the analysis has shown that Saudis opt for various functions when issuing their pledges. The cultural communicative theory effected on using linguistic forms of promising.